1990
DOI: 10.1152/jappl.1990.69.3.1137
|View full text |Cite
|
Sign up to set email alerts
|

Succinylcholine potentiates responses to intravenous acetylcholine in the canine lung periphery

Abstract: Using the wedged bronchoscope technique to measure collateral resistance (Rcs), we evaluated the effect of succinylcholine (SCh) on the response to acetylcholine (ACh) and methacholine (MCh) in the lung periphery in six mongrel dogs. Dogs were anesthetized, intubated, and mechanically ventilated. After a stable baseline Rcs was obtained, responses to intravenous ACh (25-200 micrograms), intravenous MCh (3-30 micrograms), and aerosolized ACh (30-100 micrograms/ml for 15 s) were measured. We compared the Rcs res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Thus, they concluded that the tracheal contraction induced by SCh could result from stimulation of the parasympathetic nerves rather from than a direct action on the tracheal smooth muscle. Kaise et al [3], using a fi beroptic bronchoscope technique, showed that SCh increased the canine tracheal smooth muscle contraction induced by intravenous ACh, and that this increase was not completely abolished by hexamethonium. In addition, SCh did not increase the contraction induced by intravenous methacholine or aerosolized ACh.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, they concluded that the tracheal contraction induced by SCh could result from stimulation of the parasympathetic nerves rather from than a direct action on the tracheal smooth muscle. Kaise et al [3], using a fi beroptic bronchoscope technique, showed that SCh increased the canine tracheal smooth muscle contraction induced by intravenous ACh, and that this increase was not completely abolished by hexamethonium. In addition, SCh did not increase the contraction induced by intravenous methacholine or aerosolized ACh.…”
Section: Discussionmentioning
confidence: 99%
“…Although succinylcholine (SCh) is often used as a muscle relaxant in ECT [1], its infl uence on airway reactivity has not been fully investigated. Kaise et al [3] studied a canine model, and reported that SCh probably enhanced airway reactivity to intravenous acetylcholine (ACh). Although the mechanism was not clear, they suggested that SCh might compete for plasma butyrylcholinesterase (BChE) against ACh, resulting in enhancement of ACh's action.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that cholinesterase enzymes found in the airways [5][6][7] and in the plasma [ 8] play an important role in regulating pulmonary function. Decreased cholinesterase activity is associated with both enhanced contractile responses of airway smooth muscle [ 5,6] and airway hyperresponsiveness [ 8] to acetylcholine.…”
mentioning
confidence: 99%
“…Decreased cholinesterase activity is associated with both enhanced contractile responses of airway smooth muscle [ 5,6] and airway hyperresponsiveness [ 8] to acetylcholine.…”
mentioning
confidence: 99%
See 1 more Smart Citation